TEACHING ENGLISH TO PRESCHOOL CHILDREN THROUGH GAMES - Shermamatova , Zaynab Azimjanovna; Karimova , Maftuna Mamadoliyevna; Xudoyberdiyeva , Ra’no Hakberdiyevna (Educational Research in Universal Sciences, 2023)
Since the game is the main and favorite activity of the child in kindergarten and school age, the child also discovers the world through the game. If foreign languages ​​are taught in a playful way, this will increase the efficiency of language skills acquisition several times. The game not only increases the physical activity of the child, but also helps to form mental freshness. The game helps the child to strengthen his self-confidence and to form social relations with others. Therefore, parents and educators should encourage children to learn through play as much as possible. It is through the game that children learn and discover their talents.To achieve this, it is considered appropriate to use an environment that activates sensory organs, including visual, auditory, and kinesthetic types of active education.